Neotropical osmylids (Neuroptera, Osmylidae): Three new species of Isostenosmylus Krüger, 1913, new distributional records, redescriptions, checklist and key for the Neotropical species - Martins, Caleb Califre; Ardila-Camacho, Adrian; Aspöck, Ulrike (Zootaxa, 2016)
Osmylidae is a small family of Neuroptera with a worldwide distribution. Only four subfamilies and five genera of Osmylidae have been reported to date for the Neotropical region, with a total of 16 species, whilst 200 species are known in the world. In this study three new species are described—Isostenosmylus bifurcatus n. sp., I. irroratus n. sp. and I. julianae n. sp. Moreover, species of Gumilla Navás, 1912 and Paryphosmylus Krüger, 1913 are redescribed; additionally one larva of Isostenosmylus sp. and the female of Isostenosmylus fasciatus Kimmins, 1940 are described. Images of type specimens of Neotropical species of Osmylidae are provided. New records of known species are reported and a distribution map is presented. An updated checklist and a key for Neotropical species of Osmylidae are provided.